Analisis Effect Size Pengaruh Bahan Ajar Cetak IPA Terpadu Terhadap Kompetensi Pengetahuan Siswa - N, Annisa; Festiyed, Festiyed; Asrizal, Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2021)
Humans are required to have broad insight, think critically, and be able to adapt to 21st century developments, especially in the field of education. The 2013 curriculum was created to change the mindset of students and the conceptual mastery of learning material was increased and meaningful. For that, we need integrated learning resources to support the implementation of learning. However, the problem is that the integrated science teaching materials in schools are still not integrated. One solution to overcome this problem is by analyzing the effect size of the effect of integrated science printed teaching materials on students' knowledge competencies. The type of research used is the effect size analysis. Effect size analysis is a way of summarizing and analyzing research data from several previous research results. The articles of this research consist of 20 articles. The instruments used were category codes and effect size calculations. The data analysis technique used in this study was to calculate the effect size of each article based on the mean, standard deviation, and t test. Based on the data analysis, four research results can be stated. First, integrated science printed teaching materials are equally effective at the seventh grade and eighth grade junior high school level. Second, integrated science printed teaching materials in the form of modules, books, LKS/LKPD, and teaching materials are effectively applied in science learning in junior high schools. Third, integrated science printed teaching materials have a significant influence on materials in junior high school science learning. Fourth, integrated science printed teaching materials are effective in increasing students' knowledge competencies with an effect size of 1.73. So, it can be concluded that integrated science printed teaching materials have a significant effect on students' knowledge competencies.